2024
DOI: 10.1007/s41685-024-00340-y
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing economic potential: decoding the FDI-economic growth nexus in G-15 economies amidst unique host country traits

Aastha Bajaj,
Lakshmi Bhooshetty

Abstract: The study aims to examine the impact of Foreign Direct Investment (FDI) on Economic Growth in G-15 countries while considering the in uence of key host country characteristics, namely Macroeconomic Stability, Financial Development, Human Capital, and Trade Openness. The selection of these variables is supported by both theoretical foundations and empirical studies that highlight their signi cant role in shaping the FDI-growth interconnection. Panel data derived from World Bank Indicators, spanning the period f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Iddrisu et al (2024) revealed that both financial development and globalization attract FDI in Africa. Bajaj and Bhooshetty (2024) examined the impact of FDI, macroeconomic stability, financial development, human capital, and trade openness on economic growth in the five major G-15 countries over a 33year period from 1989 to 2021. Their results showed that favorable host country characteristics amplify the impact of FDI on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Iddrisu et al (2024) revealed that both financial development and globalization attract FDI in Africa. Bajaj and Bhooshetty (2024) examined the impact of FDI, macroeconomic stability, financial development, human capital, and trade openness on economic growth in the five major G-15 countries over a 33year period from 1989 to 2021. Their results showed that favorable host country characteristics amplify the impact of FDI on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section defines the variables and principal components and summarizes the statistics for all the variables employed in the analysis. The choice of our variables has been previously proposed by studies such as Kalai et al (2024), Labidi et al (2024), , Guenichi and Omri (2024), Rajab and Zouheir (2023), Ochi et al (2024), Saidi et al (2022), Bajaj and Bhooshetty (2024), Fazaalloh (2024), Chebli and Saidi (2024), Taşdemir and Özçelik (2023), Ochi et al (2022) The endogenous variable employed in this study is economic growth. The aim of this research is to assess the effect of institutional quality, financial development, and human capital on the FDI-economic growth relationship.…”
Section: Data Descriptionmentioning
confidence: 99%